A Case Study of Migrating Gossypioma: Unforeseen Challenges - Parveen Malhotra; Vani Malhotra; Naveen Malhotra; Yogesh Sanwariya; Isha Pahuja; . Akshay (Highlights on Medicine and Medical Science Vol. 3, 2021)
Retained sponge or any surgical device following an intra-abdominal surgery is known as Gossypioma, and it is one of the most common medico-legal issues. Clinical symptoms related to intra-abdominal Gossypioma may vary from mild abdominal pain to major complications including bowel or visceral perforation, obstruction. The illness can appear in a variety of ways, from asymptomatic to serious gastrointestinal consequences such as vomiting, abdominal pain, obstruction, perforation, peritonitis, and even death. Gossypioma transmural migration is a very rare occurrence that might result in bowel or visceral perforation, obstruction, or fistula formation. The stomach, ileum, colon, bladder, vagina, and diaphragm have all been reported to have transmural migration of an intra-abdominal Gossypioma. Only a few cases have been reported in the medical literature. We do, however, disclose the first case of the world’s largest Gossypioma, a surgical mop measuring 26 x 23 cm that was successfully removed endoscopically. A 60-year-old man had an open cholecystectomy six months ago for symptomatic gall stones. After two weeks of operation intervention, he became symptomatic, complaining of abdominal pain and recurrent vomiting. A lump in the distal section of the stomach and duodenum was discovered on a barium swallow and an abdominal ultra ultrasonography, raising suspicion of gastric carcinoma. On upper gastro-intestinal endoscopy, a surgical mop that had totally migrated into the stomach and duodenum was seen. The surgical mop was successfully removed by endoscopy through the esophagus. The recovery of the patient was uneventful. Any surgical patient with unexplained chronic abdominal discomfort and vomiting should have transmural Gossypioma migration into the stomach investigated in the differential diagnosis. Endoscopy can be used for both diagnostic and therapeutic purposes. In cases of endoscopic failure or incomplete migration of Gossypioma into the stomach, surgery may be recommended.